Proteolytic cleavage of human p53 by calpain: a potential regulator of protein stability. - Kubbutat, M H (1997)
The p53 tumor suppressor protein is activated in cells in response to DNA damage and prevents the replication of cells sustaining genetic damage by inducing a cell cycle arrest or apoptosis. Activation of p53 is accompanied by stabilization of the protein, resulting in accumulation to high levels within the cell. p53 is normally degraded through the proteasome following ubiquitination, although the mechanisms which regulate this proteolysis in normal cells and how the p53 protein becomes stabilized following DNA damage are not well understood. We show here that p53 can also be a substrate for cleavage by the calcium-activated neutral protease, calpain, and that a preferential site for calpain cleavage exists within the N terminus of the p53 protein. Treatment of cells expressing wild-type p53 with an inhibitor of calpain resulted in the stabilization of the p53 protein. By contrast, in vitro or in vivo degradation mediated by human papillomavirus E6 protein was unaffected by the calpain inhibitor, indicating that the stabilization did not result from inhibition of the proteasome. These results suggest that calpain cleavage plays a role in regulating p53 stability.